Induction of autophagy in one-cell stage somatic cell nuclear transfer embryos improves preimplantation embryonic development in goat species - Nasrin Mahvash; Reza Moradi-Hajidavaloo; Farnoosh Jafarpour; Mehdi Hajian; Mohsen Rahimi; Nafiseh Sanei Ata-abadi; Marjan Sadeghi; Mohammad Hossein Nasr-Esfahani (PLoS ONE, 2025)
Autophagy is a lysosome-mediated catabolic pathway that is dependent on the mammalian target of rapamycin (mTOR). It plays a crucial role in the degradation of aged organelles and macromolecules. Several studies have explored the role of autophagy in embryonic genome activation and its significance during the early preimplantation development of mammals. In our study, we showed that autophagy is inhibited in one-cell stage SCNT embryos when compared to fertilized counterparts in goats. Notably, we found that 6-DMAP, a kinase inhibitor, reduces the phosphorylation of ERK1/2.This reduction correlates with a decrease in autophagy levels, as indicated by the presence of LC3 puncta in 6-DMAP treated embryos. To address the inhibition of autophagy in goat SCNT embryos, we induced autophagy using Rapamycin at concentrations of 10 and 100 nM for 6 hours, immediately following chemical activation. This induction led to a significant improvement in the development of goat SCNT embryos, as evidenced by an increased blastocyst rate compared to the control group. Our findings suggest that the induction of autophagy during early hours of one-cell stage embryos is critical for pre-implantation development in goat SCNT embryos warrant further investigation. This research opens new avenues for understanding the role of autophagy in embryonic development and its applications in reproductive biotechnology.